2019
DOI: 10.3233/jad-190446
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Tract-Based Analysis of Microstructural Lesions within the Alzheimer’s Disease Spectrum: Association with Amyloid Pathology and Diagnostic Usefulness

Abstract: Diffusion changes as determined by diffusion tensor imaging are potential indicators of microstructural lesions in people with mild cognitive impairment (MCI), prodromal Alzheimer's disease (AD), and AD dementia. Here we extended the scope of analysis toward subjective cognitive complaints as a pre-MCI at risk stage of AD. In a cohort of 271 participants of the prospective DELCODE study, including 93 healthy controls and 98 subjective cognitive decline (SCD), 45 MCI, and 35 AD dementia cases, we found reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Consistent with our expectation, we found an impaired transcallosal inhibition in up to 68% of cases which is in line with previously published data from independent cohorts (3,4). In contrast, however, ALS patients with MMs in the current sample did not show microstructural involvement of the corpus callosum, which is in contrast with some (22,34), but not all previous studies (39). One interpretation of the lack of corpus callosum changes in our study may be that our patients exhibited an earlier functional disturbance potentially preceding the microstructural findings in transcallosal pathways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our expectation, we found an impaired transcallosal inhibition in up to 68% of cases which is in line with previously published data from independent cohorts (3,4). In contrast, however, ALS patients with MMs in the current sample did not show microstructural involvement of the corpus callosum, which is in contrast with some (22,34), but not all previous studies (39). One interpretation of the lack of corpus callosum changes in our study may be that our patients exhibited an earlier functional disturbance potentially preceding the microstructural findings in transcallosal pathways.…”
Section: Discussionsupporting
confidence: 93%
“…For specific analysis of changes in diffusivity of individual fiber tracts we conducted a region of interest (ROI) analysis. The selection of ROIs from JHU was done as described before (34). Based on the JHU white matter atlas (35) we defined seven regions: corpus callosum with subregions genu, truncus, and splenium, corticospinal tract, and crus posterior of the internal capsula on both sides.…”
Section: Mri Data Processingmentioning
confidence: 99%
“…Also, gradual disturbances among CN, SCD, aMCI, and AD were revealed through correlation analyses between ALFF alterations and neuropsychological assessments ( Yang et al, 2018 ). DTI tractography may assist in distinguishing significantly deteriorated white matter integrity and serve as biomarkers for MCI ( Teipel et al, 2019 ; Zhang et al, 2019 ). SCD suffered from more subtle alterations than MCI, indicating a potential disease progression sequence ( Brueggen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These developments prove the accuracy of locations, support our results that these features were correlated with SUVR values, played good roles in predicting future cognitive decline (AUCs 64.9%, 72.9% and 76.1% respectively; 83.9% when combined), and probably being the imaging biomarkers of preclinical AD. Interestingly, we found the retained features only came from sMRI modality, this is probably in part due to the relatively small number of fMRI and DTI features, additionally, a latest study concluded that DTI parameters is not useful for the identi cation of preclinical AD [58] , and to the best of our knowledge, it is the rst time that texture analysis of fMRI have been applied to the eld of AD [36] . Uncertainty still exists, the signi cance of DTI and fMRI radiomics features cannot be completely denied in the exploratory study.…”
Section: Discussionmentioning
confidence: 81%